Aberrant splicing of genes involved in haemoglobin synthesis and impaired terminal erythroid maturation in SF3B1 mutated refractory anaemia with ring sideroblasts. (10th August 2015) - Conte, Simona; Katayama, Shintaro; Vesterlund, Liselotte; Karimi, Mohsen; Dimitriou, Marios; Jansson, Monika; Mortera‐Blanco, Teresa; Unneberg, Per; Papaemmanuil, Elli; Sander, Birgitta; Skoog, Tiina; Campbell, Peter; et al.
Summary: Refractory anaemia with ring sideroblasts (RARS) is distinguished by hyperplastic inefficient erythropoiesis, aberrant mitochondrial ferritin accumulation and anaemia. Heterozygous mutations in the spliceosome gene SF3B1 are found in a majority of RARS cases. To explore the link between SF3B1 mutations and anaemia, we studied mutated RARS CD34 + marrow cells with regard to transcriptome sequencing, splice patterns and mutational allele burden during erythroid differentiation. Transcriptome profiling during early erythroid differentiation revealed a marked up‐regulation of genes involved in haemoglobin synthesis and in the oxidative phosphorylation process, and down‐regulation of mitochondrial ABC transporters compared to normal bone marrow. Moreover, mis‐splicing of genes involved in transcription regulation, particularly haemoglobin synthesis, was confirmed, indicating a compromised haemoglobinization during RARS erythropoiesis. In order to define the phase during which erythroid maturation of SF3B1 mutated cells is most affected, we assessed allele burden during erythroid differentiation in vitro and in vivo and found that SF3B1 mutated erythroblasts showed stable expansion until late erythroblast stage but that terminal maturation to reticulocytes was significantly reduced. In conclusion, SF3B1 mutated RARS progenitors display impaired splicing with potential downstream consequences for genes of key importance for haemoglobin synthesis and terminal erythroid differentiation.